Juridical Review of Criminal Law Arrangements in Document Forgery Cases - Ni Made Noviana Wulandari; I Ketut Kasta Arya Wijaya (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
Document forgery is one of the criminal offenses that can damage the integrity of the legal system, affect public trust, and disrupt social order. This study aims to review the criminal law regulation related to document forgery in the Criminal Code (KUHP) and identify challenges in law enforcement. Based on the analysis of Articles 263 and 264 of the Criminal Code, it is found that criminal law in Indonesia has clearly regulated document forgery, by providing criminal sanctions to perpetrators who create, alter, or use fake documents for fraudulent purposes. However, the implementation of criminal law related to document forgery cases still faces various obstacles, such as limited evidence and the development of information technology that requires regulatory adjustments. Therefore, efforts are needed to strengthen the law enforcement system, improve legal education to the public, and adjust the rule of law to technological developments. This research provides suggestions to improve the efficiency of handling document forgery cases through strengthening coordination between legal institutions and updating relevant regulations.